UPAYA PENINGKATAN PENDAPATAN MELALUI USAHA PENGAWETAN IKAN ASIN MUJAIR DI KABUPATEN LAMONGAN - Wachidatus Sa'adah (Universitas Galuh, 2022)
Lamongan Regency is an area that has the potential to produce fishery products. If the availability of fish is abundant in the market, it will not be sold out, and it will cause losses. Fish is a food that is easily damaged (rotten). Therefore, so that fish can be utilized as much as possible, it is necessary to maintain their condition. Preservation by salting is one way to defend fish from the decay process. The commodity used is tilapia fish, the choice of tilapia because this fish is in demand by consumers, besides not having many spines, it also tastes better than other fish. The purpose of this study was to determine the level of income from the preservation of salted tilapia fish in Tumenggungan Village, Lamongan Regency. The research method used is research with a quantitative approach. The results showed that the annual income of the salted tilapia fish preservation business in Tumenggungan Village, Lamongan Regency was Rp. 478.170.000, and the R/C ratio was 1.16.